Sexting among adolescents: The role of Dark Triad in its prevalence and severity depending on sex - Penado Abilleira, Maria; Alonso del Hierro, Tara; Rodicio-García, María-Luisa (Computers in Human Behavior Reports, 2025)
Sexting is an increasingly common form of communication among adolescents. Although this is not in itself a reprehensible or harmful act, it can become dangerous if this sharing is done under pressure, in a non-consensual manner, or has negative consequences for one of the parties involved. For this reason, this study aims to explore in depth the characteristics of the Dark Triad that may be related to the distribution of intimate images in the adolescent population and to investigate the possible differences in this relationship based on sex. Data were collected from a sample of 1570 adolescents aged 13 to 18. The results show a greater sexting behavior by girls, especially when it is carried out through social networks. Similarly, narcissistic and psychopathic traits are the traits most strongly associated with the presence and severity of image-sharing behavior in both boys and girls, with their importance varying according to the medium in which the image exchange takes place. Only Machiavellian traits seem to be associated with the occurrence of sexting among girls when it is done via mobile phones. In short, dark personality traits are relevant factors in the presence and severity of image-sharing behavior among adolescents, with differences observed according to the sex of the adolescents and the technological medium used.
Keywords: adolescents; machiavellianism; narcissism; psychopathy; sex; sexting